106 Evaluation of participant feedback from a group based pain education sessions for young people aged between 9–18 years old and their parents. (4th October 2017) - Lilley, S; Peters, J; Grey, S; Samuel, M; Sapochnik, M; McCarthy, K; Keen, K; Jay, M; Howard, R
Abstract : Background: Pain education is effective in increasing understanding and reducing disability when implemented early in adult pain management (British Pain Society, 2013). However, less research has been undertaken into the benefits of this for young people. Great Ormond Street Hospital Pain Control Service observed that Pain education provided in clinic settings were often poorly retained by young people and their families. Therefore, Pain Education Sessions were developed and implemented to target this. Methods: Stand-alone sessions were run with 4–8 young people aged between 9–18 years old. Each young person attended with at least one parent/carer. The sessions lasted 3 hours and covered topics including pain mechanisms, medication management, pacing, relaxation, distraction techniques and healthy thinking. A multi-professional approach to planning and delivery was utilised, including psychology, physiotherapy, nursing and medical input. Feedback was collected via anonymous forms from young people and carers who attended. Results: The feedback suggested that 93% of young people and 97% of parents felt the sessions were helpful or very helpful. Participants indicated that they benefited greatly from meeting others with chronic pain. The feedback highlighted that many participants found the pain mechanisms and medication management topics most helpful. Conclusion: Feedback from young people and parents who participated indicates that Pain Education Sessions were helpful to aid understanding of chronic pain and management strategies available. Sessions were evaluated favourably by all who attended and suggested they would recommend this to other people with chronic pain. Further research into the impact of pain education sessions on the long term outcomes of young people with chronic pain is required.